What content offers and how teachers teach: Religious Moderation-integrated teaching in Indonesia - Hanafi, Yusuf (HTS teologiese studies, 2023)
What and how to teach religious moderation at the undergraduate level still concerns academics. This study aims to explore the perceptions of lecturers and students about the objectives, content, and strategies used in learning religious moderation. This study uses a multiple-case exploratory design with a qualitative approach. Data were collected through interviews with eight lecturers and 15 students from public and Islamic universities in Indonesia. Data analysis in this study used conventional content analysis methods with an inductive coding process. The first two authors analysed data, and their agreement was calculated using Cohen’s kappa of 0.90. As a result, participants said that the ultimate goal of learning moderation in religion is to teach students about aligning views on religion and non-religion. The content that needs to be taught early and as a firm root of religious moderation is the internal harmony of religious communities. Finally, the development of campus culture can be an alternative model to internalise the values of religious moderation.Contribution: Overall, this research helps us to understand what kind of religious moderation learning we want to introduce in Indonesian universities.